Fish-scale inspired superoleophobic membrane from cellulose: A Review - Halim, Abdul; Ismayati, Maya; Gabriel, Azmi Alvian; Ihsanpuro, Surya Iryana; Medy, Nabil Septian; Muharja, Maktum; Enomae, Toshiharu (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Nature-inspired technology has been investigated widely. Anti biofouling properties of fish scale has inpired to improve membrane performance. Biofouling affects an oil-water separation membrane. The bacterial, coagulant, and hydrophobic oils attach to the membrane surface, demanding periodic cleaning. To overcome the problems, surface modification materials are introduced namely superoleophobic surface. The superoleophobic surface promises antifouling, high flux, and high separation efficiency. Superoleophobic surfaces are inspired by the scales on fish that form a hydrogel-like layer on their surface. The hydrogel repels oil and any organic materials, keeping the surface clean. The hydrogel of fish scales can be mimicked by cellulose-based materials. A dense layer of hydroxyl groups absorbs a lot of water and forms a hydrogel bond. The membrane with the cellulose hydrogel-like structure will perform a superoleophobic characteristic surface. The characteristic can be utilized as a functional membrane for oil-water separation. This article reviews the principle, mechanism, current development, and future challenges of bioinspired superoleophobic surfaces from cellulose-based materials for membrane applications.